Comparison of the clinical effects of reverse digital artery island flap and dorsal branch digital artery island flap on digital tip reconstruction: a single-center retrospective study - Yue Pan; Jun Lei; Jun Yang; Mingwei Dong; Shengjie Jiang; Guangchen Sun; Hui Yu (Journal of Plastic Surgery and Hand Surgery)
Background: This study aimed to compare the repairing effects of reverse digital artery island flap and dorsal branch digital artery island flap on fingertip defects.